Covid-19: Selebgram Bicara, Selebgram Bertindak - Yuni Khaerunnisa Arta (Emik, 2021)
The Covid-19 pandemic has greatly impacted on Indonesian life. Various efforts have been made by the government by issuing various policies, from implementing health protocols, Work From Home (WFH), large-scale social restrictions (PSBB), to the implementation of office activity restrictions (PPKM). To break the chain of transmission of Covid-19, even though the government is responsible for handling Covid-19, this is not only the duty of the government, but it is the joint duty of various elements of society, including the celebgram. This article deals with the role of celebgram in helping the government to break the chain of transmission of Covid-19. This qualitative research was conducted in the city of Makassar as one of the cities in Indonesia that has experienced twice large-scale social restrictions (PSBB). Data was collected by combining in-depth interviews and observation. There were ten informants participated in this study, whose age are varied between 19 and 27 years, and four of them are university students. All of the informants work as celebgrams, but seven of them have multiple professions: four of them are celebgrams and freelancers, two of them are celebgrams and entrepreneurs; and one of them has triple professions, as a celebgram, model, as well as freelancer. The study indicated that influencers such as celebgrams have a great opportunity to influence their followers because celebgrams are considered role models or people whose attitudes and behavior are imitated by their followers. To educate people in relation to Covid-19, celebgrams equip themselves with good and correct knowledge about Covid-19 which obtained from various sources, ranging from the internet, social media, television and other trusted sources of information. In doing so, celebgram have different metods, such as providing education through social media or going directly to the community. Education through social media is carried out in the form of live Instagram, creating educational videos regarding the importance of health protocols, and uploading them on their respective social media accounts. In addition, the celebgram also made efforts to prevent the transmission of the Covid-19 virus by going directly to the field which was carried out in the form of spraying disinfectants and distributing health protocol packages, such as hand sanitizers, masks and educational posters. They did this not as a public paid endorser, but as a form of moral responsibility to help the government in overcoming Covid-19. It is argued in this article that celebgram plays an important role in helping the government to break the chain of transmission of Covid-19.